2022
DOI: 10.1021/acs.inorgchem.2c00241
|View full text |Cite
|
Sign up to set email alerts
|

Further Insight into the Conversion of a Ni–Fe Metal–Organic Framework during Water-Oxidation Reaction

Abstract: Metal–organic frameworks (MOFs) are extensively investigated as catalysts in the oxygen-evolution reaction (OER). A Ni–Fe MOF with 2,5-dihydroxy terephthalate as a linker has been claimed to be among the most efficient catalysts for the oxygen-evolution reaction (OER) under alkaline conditions. Herein, the MOF stability under the OER was reinvestigated by electrochemical methods, X-ray diffraction, X-ray absorption spectroscopy, energy-dispersive spectroscopy, scanning electron microscopy (SEM), transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 99 publications
(152 reference statements)
1
7
0
Order By: Relevance
“…Due to a relatively better alkaline stability of NiWO 4 over the analogous NiMoO 4 , the surface oxidation could presumably be less pronounced. 40 In addition to the redox feature in CV recorded between 0.89 and 1.95 V (vs RHE), the Raman data obtained with the electrode after 10 CV cycles also strikingly resembled the fresh NiWO 4 catalyst (Figure 7a primarily NiO(OH) ED /NF, as mentioned above. The polarization curve obtained from the LSV showed a redox peak at around 1.35 V, followed by a sharp increase in the current density to 175 mA cm −2 at 1.62 V (vs RHE) (Figure 8a).…”
Section: ■ Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Due to a relatively better alkaline stability of NiWO 4 over the analogous NiMoO 4 , the surface oxidation could presumably be less pronounced. 40 In addition to the redox feature in CV recorded between 0.89 and 1.95 V (vs RHE), the Raman data obtained with the electrode after 10 CV cycles also strikingly resembled the fresh NiWO 4 catalyst (Figure 7a primarily NiO(OH) ED /NF, as mentioned above. The polarization curve obtained from the LSV showed a redox peak at around 1.35 V, followed by a sharp increase in the current density to 175 mA cm −2 at 1.62 V (vs RHE) (Figure 8a).…”
Section: ■ Introductionsupporting
confidence: 68%
“…A detectable increase in the current density in the higher applied potential region, above 1.6 V (vs RHE), indicated that upon redox cycling, there is a generation of more number of catalytically active Ni­(III) sites on the NiWO 4 surface to enhance the OER. Due to a relatively better alkaline stability of NiWO 4 over the analogous NiMoO 4 , the surface oxidation could presumably be less pronounced . In addition to the redox feature in CV recorded between 0.89 and 1.95 V (vs RHE), the Raman data obtained with the electrode after 10 CV cycles also strikingly resembled the fresh NiWO 4 catalyst (Figure a,b).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, metal–organic frameworks (MOFs) have been reported as efficient catalysts for WOR . Although the WOR mechanism and active sites are enigmas, , MOF decomposition and metal (hydr)­oxide formation during WOR should be carefully investigated. , Deibert et al reported that the decomposition of a Mn 4 O 4 -based MOF results in MnO x formation, as a true catalyst under photochemical WOR conditions . Organic ligands and thermodynamically favorable MnO x formation are a driving force toward MOF decomposition.…”
Section: Conversion Of Mn Complexes To Mn Oxidementioning
confidence: 99%
“…The details of OER in the presence of Ni coordination compounds have been thoroughly investigated. During OER in the presence of a Ni coordination compound, one should be attentive to the role of the Ni (hydr)­oxide formed toward OER. However, pure Ni (hydr)­oxide is a poor catalyst for OER, but when Fe as an additional compound or as an impurity is combined with Ni (hydr)­oxide, it forms one of the most efficient OER catalysts under alkaline conditions. , …”
Section: Introductionmentioning
confidence: 99%